Vocal cord paralysis following central line insertion in a neonate: a review of the literature. (15th July 2011) - Arshad, Faisal A; Eng, Chee Yean; Daw, William; Thevasagayem, Mahilravi S; Bateman, Neil
Abstract : Acute onset stridor in a neonate following general anaesthesia is commonly attributed to laryngeal oedema secondary to anaesthetic airway trauma. The authors present a case of recurrent laryngeal nerve injury resulting in vocal cord paralysis causing stridor following central venous catheterisation under general anaesthesia in a neonate. This was managed expectantly and resolved spontaneously over a period of 6 months.